Mekanisme Penyelesaian Konflik Nelayan (Studi di Pantai Puger Kabupaten Jember) - Aan Eko Widiarto; Setiawan Nurdayasakti; Faizin Sulistio (Jurnal Hukum PRIORIS, 2013)
Interaction among fisherman in the activity of fishing is potential to result conflict. Factor of the conflict can be related to the area of fishing, equipments of fishing and attitudes. These kinds of conflict can be categorized as horizontal conflict. Besides, vertical conflict can also happen in the communty of fisherman. The conflicts happen among the fisherman and government. Policies of the government, especially the policies that are not in accordance with the fisherman need can be the factor of conflicts. The policy of the government, especially local government that is not in accordance with the fisherman need is the policy to explore the natural resourches. This policy is based on the government need to increase the income. This research learn the mechanisms that are applicated by the fisherman to solve the conflict. They have their own internal mechanism to solve the conflict. This kind of mechanism have raised among their community since long time ago.